OPTIMALISASI KEUANGAN MAHASISWA MELALUI LITERASI KEUANGAN DAN PEMANFAATAN TEKNOLOGI FINANSIAL - Vivia Irvani; Dwi Eko Waluyo; Dian Prawitasari (MANAJEMEN, 2025)
This study aims to examine the factors influencing students' financial management behavior, focusing on the roles of financial attitude, financial knowledge, and internal locus of control, while also considering financial technology as a moderating variable. Data were collected from 196 students at Dian Nuswantoro University and Semarang State University using a Likert-scale questionnaire. The findings indicate that financial attitude and financial knowledge significantly influence financial management behavior. Furthermore, financial knowledge significantly affects internal locus of control, which in turn influences financial management behavior. However, financial technology does not moderate the relationship between internal locus of control and financial management behavior. These results highlight the importance of comprehensive financial literacy and the prudent use of financial technology to support effective financial management among university students.